2016
DOI: 10.1055/s-0035-1561451
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Alkynyl-1,4-cyclohexadienes via a Diels–Alder Reaction of Conjugated 2,4-Diynones

Abstract: General Methods. All reactions were performed in flame-dried glassware under a N 2 atmosphere. Solvents were degassed and dried by standard methods before use. Purification of the crude products was carried out by column chromatography using silica gel. Analytical TLC was performed on a silica gel GF 254 plate. The TLC plates were visualized under ultraviolet (UV, 254 nm) light or by staining with PMA or CAM. NMR spectra were recorded on a 400 or 500 MHz NMR spectrometer in CDCl 3. Proton chemical shifts are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…In the case of the devices presented in this study, the crossover of oxygen is expected to be lower than that measured for H 2 , as its permeability in Nafion is lower. 40,41 …”
Section: Gas Transport Across Channelsmentioning
confidence: 99%
“…In the case of the devices presented in this study, the crossover of oxygen is expected to be lower than that measured for H 2 , as its permeability in Nafion is lower. 40,41 …”
Section: Gas Transport Across Channelsmentioning
confidence: 99%
“…[22][23][24][25] Surprisingly, only very limited pure-gas transport data have been reported for Nafion ® . [26][27][28][29][30][31] The first comprehensive study on the gas permeation properties of dry Nafion ® was reported by Chiou and Paul using the constant volume/variable pressure technique. 29 The gas diffusion coefficients were then deduced from the time-lag method.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30][31] The first comprehensive study on the gas permeation properties of dry Nafion ® was reported by Chiou and Paul using the constant volume/variable pressure technique. 29 The gas diffusion coefficients were then deduced from the time-lag method. Their study indicated low permeability in dry Nafion ® for all gases other than He and H 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations